Sodium-glucose cotransporter 2 inhibitors as potential anticancer agents - E. R. Radkevich; A. S. Severina; M. S. Shamkhalova; M. V. Shestakova (Сахарный диабет)
Oncological diseases are one of the leading causes of mortality in the world. Despite the intensive search for new methods to increase the efficacy and safety of antineoplastic therapy and to reduce resistance to it by malignant tumors, treatment issues still remain unresolved in clinical oncology. This review analyses experimental data on the antineoplastic effect of sodium-glucose cotransporter 2 (SGLT2) inhibitors: the reasons why SGLT2 inhibitors can be used for the treatment of malignant tumors are presented, class-specificity and dose-dependence of the antineoplastic effect of the drugs are determined. Possible mechanisms of antitumor effect of glyflozins are described in detail, among which, in addition to reduction of glucose entry into tumor cells, inhibition of Wnt/β-catenin signalling pathway, enhancement of AMP activated protein kinase activity with subsequent change of lipid profile of tumor cells and inhibition of mTOR protein kinase (mammalian target of rapamycin), disruption of DNA and RNA synthesis in malignant tumor cells, etc. play a significant role. Considerable space is devoted to the pro-oncogenic effect of SGLT2 inhibitors, previously undisputed and now disproved, as well as to the interaction of this class of antidiabetic agents with other antitumor treatment in the context of efficacy, safety and therapeutic resistance.